Academic dishonesty on online learning among vocational high school students - Surya Jatmika; Joko Suwandi; Faizah Laila Oktaviana; Mutiara Karima; Jarot Tri Bowo Santoso (Institute of Advanced Engineering and Science, 2022)
This study described the academic dishonesty phenomenon in accounting subject online learning at the business and management vocational high schools and identify the factors that influenced students to commit academic dishonesty. This was case study research with a qualitative approach. The participants were four teachers and six students from accounting and institutional finance classes. The data were collected using interviews and documentation, then being analyzed using interactive analysis techniques. The results showed that most students’ academic dishonesty behaviors were cheating and collaborating during examinations or assignments and doing individual assignments together. Several factors related to academic dishonesty among students include: i) Rationalization, stating rational reasons about the teacher not explaining the material thoroughly, which impacted students’ lack of material understanding; ii) Pressure, which comes from a desire within the students and parents’ demands to get good grades; iii) Opportunity, which arises due to the lack of direct teacher supervision on students’ work and the openness of internet access; and iv) Lack of academic ability, showing that the students who commit academic dishonesty are usually lacking in terms of academic ability.